From Chaos to Control: Programmable Crack Patterning with Molecular Order in Polymer Substrates. Issue 22 (15th April 2021) - Kim, Hyun; Abdelrahman, Mustafa K.; Choi, Joonmyung; Kim, Hongdeok; Maeng, Jimin; Wang, Suitu; Javed, Mahjabeen; Rivera‐Tarazona, Laura K.; Lee, Habeom; Ko, Seung Hwan; Ware, Taylor H.
Abstract: Cracks are typically associated with the failure of materials. However, cracks can also be used to create periodic patterns on the surfaces of materials, as observed in the skin of crocodiles and elephants. In synthetic materials, surface patterns are critical to micro‐ and nanoscale fabrication processes. Here, a strategy is presented that enables freely programmable patterns of cracks on the surface of a polymer and then uses these cracks to pattern other materials. Cracks form during deposition of a thin film metal on a liquid crystal polymer network (LCN) and follow the spatially patterned molecular order of the polymer. These patterned sub‐micrometer scale cracks have an order parameter of 0.98 ± 0.02 and form readily over centimeter‐scale areas on the flexible substrates. The patterning of the LCN enables cracks that turn corners, spiral azimuthally, or radiate from a point. Conductive inks can be filled into these oriented cracks, resulting in flexible, anisotropic, and transparent conductors. This materials‐based processing approach to patterning cracks enables unprecedented control of the orientation, length, width, and depth of the cracks without costly lithography methods. This approach promises new architectures of electronics, sensors, fluidics, optics, and other devices with micro‐ and nanoscale features. Abstract : Cracks are normally classified as material failures to be prevented. A crack patterning strategy is described that allows freely programmable patterns of cracks guided by the alignment of liquid crystal polymer networks. This programmable cracking enables high‐resolution patterning in a high‐throughput manner without the use of expensive lithography procedures and may serve as an alternative fabrication strategy for various applications.